Acute pulmonary exacerbation and lung function decline in patients with cystic fibrosis: high-mobility group box 1 (HMGB1) between inflammation and infection. (April 2015) - Chirico, V.; Lacquaniti, A.; Leonardi, S.; Grasso, L.; Rotolo, N.; Romano, C.; Di Dio, G.; Lionetti, E.; David, A.; Arrigo, T.; Salpietro, C.; La Rosa, M.
Abstract: Airway inflammation plays a central role in cystic fibrosis (CF) lung disease, and biomarkers of inflammation, such as high-mobility group box 1 (HMGB1) could be used to monitor disease activity. The main aim of this study was to confirm the role of HMGB1 in CF patients, correlating its serum and sputum levels with pulmonary function and inflammation. Serum and sputum HMGB1 were evaluated in a cohort of 31 CF patients and 30 non-smoking healthy subjects (HS group). Acute pulmonary exacerbation events and lung function decline have been also evaluated during a 3-year follow-up period. Serum HMGB1 levels were significantly higher than those measured in HS, such as sputum HMGB1. Kaplan-Meier survival curves revealed that patients with high HMGB1 values experienced a significantly faster evolution to decline of lung function. A multiple Cox regression analysis assessed that an increase of serum HMGB1 was associated with 5% increased risk of pulmonary disease progression, whereas elevated sputum HMGB1 was related to a 10% increased risk of lung function decline. In CF patients, HMGB1 closely reflects the entity of pulmonary impairment and represents a strong and independent risk marker for progression of lung function decline.